PENINGKATAN KEMAMPUAN LITERASI PEMUDA ELELIM DI DISTRIK ELELIM KABUPATEN YALIMO PAPUA - Linus Yhani Chrystomo; Efray Wanimbo; Puguh Sujarta (JURNAL PENGABDIAN PAPUA, 2020)
Literacy programs in the form of community service in Elelim Village can be a means to develop the knowledge and potential of local local communities so that they have broad understanding, literacy skills and adequate competence. The community can explore and empower all potentials of the region to the maximum to support the progress of the community and the region. Literacy programs in the local community in Elelim Village can also develop the values of local wisdom that are part of people's lives. The youth or youth community has a role in the development of the nation's future and the dynamics of youth in the journey of national life determine the future direction of the Indonesian nation. The aim of community service literacy program is to increase the literacy ability of Elelim youth in Elelim Village, Yalimo Regency, Papua. The method used is a lecture method that approaches the local cultural character or adapts according to the culture of the local community. And the accompanying educational method by providing examples or symbols to improve literacy skills with any objects, plants or animals in the local area. So that its to improve youth literacy skills in the Elelim Village. The results of community service can be concluded that the motivation and enthusiasm of the Elelim young generation's willingness in studying literacy can improve the literacy ability of Elelim youth in Elelim District, Yalimo Regency, Papua. Keywords: Literacy programs service, Youth Elelim Village, Regency Yalimo, Papua